Fetal heart rate tracing interpretation in cases of fetal heart block: A case series. Issue 2 (13th February 2022) - Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Traisrisilp, Kuntharee; Jatavan, Phudit; Tongsong, Theera
Abstract: Simple assessment of FHR baseline variability can differentiate second‐degree heart block (SHB) from complete heart block (CHB). In cases of SHB, antepartum NST can be reliably used for fetal surveillance. Intrapartum assessment of FHR variability and accelerations is useful to select cases for safe vaginal delivery. Abstract : Fetal heart rate tracings of second‐degree heart block (SHB) fetuses still represent SA node function depending on sympathetic and parasympathetic tone, reflective of fetal hypoxic status. NST and intrapartum FHR tracings are reliable. On the contrary, FHR tracings of cases with complete heart block (CHB), as well as sinus arrhythmia, are independent from SA node impulses, representing solely ventricular rate, not reflective of SA node rate variability and CNS hypoxic status. Therefore, the interpretation in the fetuses with CHB is unreliable to determine fetal well‐being.